Evaluating Deceased Donor Registries: Identifying Predictive Factors of Donor Designation. Issue 3 (March 2013) - Hajhosseini, Babak; Stewart, Bryan; Tan, Jane C.; Busque, Stephan; Melcher, Marc L.
The objectives of this study were to evaluate and compare the performance of the deceased donor registries of the 50 states and the District of Columbia and to identify possible predictive factors of donor designation. Data were collected retrospectively by Donate Life America using a questionnaire sent to Donor Designation Collaborative state teams between 2007 and 2010. By the end of 2010, there were 94, 669, 081 designated donors nationwide. This accounted for 39.8 per cent of the U.S. population aged 18 years and over. The number of designated organ donors and registry-authorized recovered donors increased each year; however, the total number of recovered donors in 2010 was the lowest since 2004. Donor designation rate was significantly higher when license applicants were verbally questioned at the Department of Motor Vehicles (DMV) regarding their willingness to register as a donor and when DMV applicants were not given an option on DMV application forms to contribute money to support organ donation, compared with not being questioned verbally, and being offered an option to contribute money. State registries continue to increase the total number of designated organ donors; however, the current availability of organs remains insufficient to meet the demand. These data suggest that DMV applicants who are approached verbally regarding their willingness to register as a donor and not given an option on DMV application forms to contribute money to support organ donation might be more likely to designate themselves to be a donor.